MOOC construction for life education in Chinese universities: an analytical study - Xu, Fengling; Zhang, Junqing; Zhou, Qiqi; Mou, Shaoyu (Frontiers in Public Health, 2025)
BackgroundWith the advancement of the Chinese “Internet Plus” paradigm, life education has expended through the implementation of Massive open online courses (MOOCs). However, limited research has focused on the present condition and attributes of the building of Chinese life education MOOCs.ObjectivesTo systematically analyze the current status and attributes of life education MOOCs in China, assess the quality of the courses, and give a reference for the development of life education MOOCs in the country.MethodsWe select China’s online education platform and utilize the search terms “Health OR Life OR Death OR Psychology OR Nutrition OR Exercise OR Well-being OR Love OR Ethics” to identify MOOCs pertinent to life education. Analyze and summarize the courses about platforms, schools, regions, objectives, contents, assessments, credit hours, number of sessions and number of learners. The quality of the course was assessed utilizing Quality Matters (QM).ResultsIn China, 129 life education MOOCs were provided in six online education platforms. The quantity of courses originating from “double first-class” universities, general universities and higher vocational universities was 44, 40, and 45, respectively. The quantity of courses from eastern regions was 106, while from western regions it was 23. The course contents covered three domains: life education, death education, and life value education. Credit hours, course sessions and the number of course learners exhibit statistically significant differences among regions and school types (p < 0.05). 47.3% of the QM scores were 60–84%, indicating subpar overall course quality. 19 life education MOOCs were provided in foreign platforms Coursera and edX, with 52.6% having course duration of less than 16 h and 47.4% catering to over 100,000 participants.ConclusionChinese life education MOOC is resource-rich and has a substantial learner base. However, issues persist, including inconsistent course quality, limited personalization of course content, and significant disparities between eastern and western regions. In the future, Chinese life education MOOC should align with the development in Artificial Intelligence (AI) technology, address the disparities between Eastern and Western areas, and integrate with worldwide platforms.